THE ROLE OF CREATIVE AND INNOVATIVE EDUCATION MANAGEMENT IN IMPROVING THE QUALITY OF LEARNING - Loso Judijanto; Zoni, Lapas; Sappaile, Baso Intang (Adisam Publisher, 2024)
Creative and innovative educational management can help overcome the challenges faced by teachers in carrying out their duties. With a clear framework, teachers can have a guide that can help them organize their workload, plan learning, and cope with changes in policy and curriculum. Effective educational management can also provide the support, training, and supervision needed for teachers to continue to develop themselves and improve the quality of their teaching. The quality of learning is centered on the teacher's ability during the learning process in the classroom. Teachers are required to have the ability to plan learning, in the learning process, and in evaluating learning. When educators put forth the proper effort in imparting knowledge in accordance with the character traits of their students and the constraints of their teaching time, their attempts to apply teacher innovation and creativity management to enhance the quality of learning can succeed. Enhancing the quality of learning is largely dependent on creative and inventive educational management through innovation in the development of educational multimedia, the role of the principal in integrated quality management, the development of creative and innovative learning media, and the management of facilities and infrastructure.